2021
DOI: 10.1039/d0cp05221c
|View full text |Cite
|
Sign up to set email alerts
|

Half metallicity and ferromagnetism of vanadium nitride nanoribbons: a first-principles study

Abstract: Half metallic vanadium nitride nanoribbons with intrinsic ferromagnetism and 100% spin filtering efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…The use of strain engineering in two-dimensional heterostructures to modulate their electronic and optical properties is a generally accepted approach. [38][39][40][41][42][43] Therefore, we also studied one response of band gap and the absorption spectrum of the heterostructure of 3L-Ga-GaN/MgI 2 under biaxial strain. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of strain engineering in two-dimensional heterostructures to modulate their electronic and optical properties is a generally accepted approach. [38][39][40][41][42][43] Therefore, we also studied one response of band gap and the absorption spectrum of the heterostructure of 3L-Ga-GaN/MgI 2 under biaxial strain. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional materials are expected to have widespread applications not only in the electronic devices, but also in the energy storage applications, for example, supercapacitors and batteries, because of their extraordinary structural, electronic, and mechanical properties and enlarged surface areas. , High storage capacity, charge/discharge rate and cycling lifes are important characteristics of alkali metal ion battery which are primarily goverened by the properties of cathode materials. To enhance the electrochemical performance, it is emergent to design the suitable cathode materials. , Among the two-dimensional materials, graphene rises as efficient anode material with a specific capacity of 540 mAh/g and defective graphene with a specific capacity range between 1071 to 1450 mAh/g. , Two dimensional transition metal dichalcogenides (MoS 2 , WS 2 , VS 2 ), , transition metal carbides (also known as MXenes; Mo 2 C, Ti 3 C 2 , V 2 C), metal nitrides (TiN, VN, CrN, MnN), metal oxides, and BP 2 monolayers are expected and are obtained as the high performance anode and cathode materials for lithium- and sodium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Edge reconstruction is a common strategy to solve this problem, improve the stability of the system and even endow nanoribbons with exotic electronic properties. 11,12 Chen et al 10 found that the Se : Mo ux ratio can control the morphologies of MoSe 2 nanoribbons during growth, forming a Mo-or Se-terminated edge. Similarly, it has been found that different edge passivation modes can endow MoS 2 nanoribbons with different electronic characteristics, such as metallic or semiconducting properties as well as ferromagnetic or non-magnetic behaviors.…”
Section: Introductionmentioning
confidence: 99%